An integrative influence of saline water irrigation and fertilization on the structure of soil bacterial communities. (26th December 2019) - Chen, L. J.; Li, C. S.; Feng, Q.; Wei, Y. P.; Zhao, Y.; Zhu, M.; Deo, R. C.
Abstract: Although numerous studies have investigated the individual effects of salinity, irrigation and fertilization on soil microbial communities, relatively less attention has been paid to their combined influences, especially using molecular techniques. Based on the field of orthogonal designed test and deoxyribonucleic acid sequencing technology, the effects of saline water irrigation amount, salinity level of irrigation water and nitrogen (N) fertilizer rate on soil bacterial community structure were investigated. The results showed that the irrigation amount was the most dominant factor in determining the bacterial richness and diversity, followed by the irrigation water salinity and N fertilizer rate. The values of Chao1 estimator, abundance-based coverage estimator and Shannon indices decreased with an increase in irrigation amount while increased and then decreased with an increase in irrigation water salinity and N fertilizer rate. The highest soil bacterial richness and diversity were obtained under the least irrigation amount (25 mm), medium irrigation water salinity (4.75 dS/m) and medium N fertilizer rate (350 kg/ha). However, different bacterial phyla were found to respond distinctively to these three factors: irrigation amount significantly affected the relative abundances of Proteobacteria and Chloroflexi; irrigation water salinity mostly affected the members of Actinobacteria, Gemmatimonadetes and Acidobacteria; and N fertilizer rate mainly influenced the Bacteroidetes' abundance. The results presented here revealed that the assessment of soil microbial processes under combined irrigation and fertilization treatments needed to be more careful as more variable consequences would be established by comparing with the influences based on an individual factor, such as irrigation amount or N fertilizer rate.